Analysis of peri-urban landscape composition and its spatio-temporal transformations: the case of the Metropolitan District of Quito - Ortiz-Báez, Paola; Freire, Maria José; Bogaert, Jan (Journal of Architecture and Urbanism, 2023)
Latin American contemporary cities are facing a rapidly urban dispersion which is mainly occurring in periurban zones. Since these transitional spaces remain geographically and conceptually unclear, having a greater understanding of its landscape composition has become a key issue for territorial planning purposes. In this article, the Metropolitan District of Quito urban-rural gradient landscape composition and its spatiotemporal transformations are analysed. Using satellite images of very high resolution of two periods, five Land Use-Land Covers (LULC) were identified in sixty-four sample polygons. Based on that, a transition matrix and a stability index were developed to analyse landscape composition change intensity. Results demonstrate that peri-urban areas show the highest landscape instability, although through a great diversity of land occupation typologies. The four dominant typologies are analysed. Parsing LULCs independently, vegetation showed the greatest instability, which significantly alters ecosystems and their services. On the other hand, mega-road infrastructure appears to be one of the most dramatic drivers of peri-urban transformation, since samples crossed by new highways experienced the greatest landscape transformation on average. Finally, this methodology and insights could be extrapolated to other Latin American cities, where micro-scale policymaking should be a priority in scenarios of complex and highly heterogeneous peri-urbanization.